KURIKULUM MERDEKA: PERAN GURU PAI DALAM MEMBENTUK KARAKTER SISWA DI ERA DIGITAL - Repi, Predi Ari; Abdullah, Radhinal; Halimah, Siti (Universitas Al-Amien Prenduan, 2024)
The freedom of teachers and students is the essence of self-oriented learning, capable of producing high-quality education, internationally recognised. In teaching learning activities, the role of the teacher is no longer the primary medium of instruction. Students can now quickly retrieve knowledge from a variety of media and learning resources that grow with technological developments, whether in terms of IT-based learning or other forms of communication. This research takes a qualitative approach, using library research methods to gather previous research data sources with correlation. Access to initiation data sources in Google Scholar, as well as other research related articles. The findings highlight the importance of PAI teacher competence in the independent curriculum learning process in the digital age. Given that Islamic education contains a large amount of material that is important to students, such as the Quran Hadith, Fiqih, and Akidah Akhlak, a PAI teacher should use digital media, social media, and search engines to find relevant material, as well as support the PAI learning process in an independent curriculum in the digital age.